2020
DOI: 10.1177/0963689720912688
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Endothelial Progenitor Cells in the Treatment of Coronary Artery Microembolism in Rats

Abstract: As the impairment of myocardial microenvironments due to coronary microembolization (CME) compromises the treatment effect of percutaneous coronary intervention and leads to adverse prognosis, we hypothesized that endothelial progenitor cells (EPCs) transplantation could improve cardiac function in the condition of CME. Low- (2 × 105) and high- (2 × 106) dose rat bone marrow-derived EPCs were transplanted in a model of CME. To develop a CME model, rats were injected with autologous micro-blood-clots into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…ECFCs have been shown to promote the formation of new endothelium in animal models, in which vessel injury occurs after balloon injury, myocardial infarction, or coronary microembolization [ 35 – 37 ]. Exosomes have emerged as an important paracrine mechanism of cell-to-cell communication by facilitating the transfer of RNAs or proteins from one cell to a recipient cell [ 38 ], and their use is currently considered to represent a promising alternative to stem cell therapy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECFCs have been shown to promote the formation of new endothelium in animal models, in which vessel injury occurs after balloon injury, myocardial infarction, or coronary microembolization [ 35 – 37 ]. Exosomes have emerged as an important paracrine mechanism of cell-to-cell communication by facilitating the transfer of RNAs or proteins from one cell to a recipient cell [ 38 ], and their use is currently considered to represent a promising alternative to stem cell therapy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…EPCs have been reported, which have role in vasculogenesis, angiogenesis, and re-endothelialization of injured vessels. Recently, study by Xue et al indicates that even low-dose of EPCs transplantation may play a pro-angiogenic, anti-fibroblast, anti-fibrosis, and antinecrosis role and enhance cardiac function in a rat model [13]. The EPCs angiogenic potential limited by the absence of their natural biologic foundation, namely, smooth muscle pericytes also known as smooth muscle cells (SMCs); EPC-SMCs cell sheet transplantation attenuated myocardial dysfunction [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a myocardial ischemia–reperfusion model, EPCs and EPC-derived conditioned medium enhanced tissue regeneration and improved ischemia-related organ dysfunction by inhibiting oxidative stress (oxidative proteins and markers of oxidative stress), autophagy (LC3B-I and LC3B-II), apoptosis (cleaved caspase 3 and cleaved PARP) and fibrosis (Smad3 and TGF-ß)-associated marker expression ( 116 ). Studies have shown that miR-214 expression was upregulated in EPCs and may have regulated CM Ca2+ homeostasis and cell survival during myocardial ischemia injury through miR-214 ( 117 , 118 ). Hong et al found that crosstalk between ECs and CMs was critical for regulating CM function and that vascular networks generated by ECFCs enhanced the engraftment of human pluripotent stem cells.…”
Section: Epc Recruitment-related Signaling Pathwaysmentioning
confidence: 99%
“…Reduced basic fibroblast growth factor and increased angiogenesis in ischemic hearts after EPC EX treatment reduced the area of cardiac fibrosis. Therefore, it was inferred that the proangiogenic function of EPC-derived EXs may be partially attributable of the activated MEndT of CFs ( 117 ). However, how EPC-derived EXs regulate the MEndT has not been elucidated to date.…”
Section: Epc Recruitment-related Signaling Pathwaysmentioning
confidence: 99%